Enhancing Mathematics Learning Outcomes Through Stad Cooperative Model In Grade V - Nurmawati Nurmawati; Asnita Hasibuan (Journal on Education, 2024)
Abstract This classroom action research, conducted in two cycles, aimed to explore the effectiveness of implementing the STAD (Student Teams Achievement Division) type cooperative learning model in improving Mathematics learning outcomes for grade V pupils. Each cycle involved planning, action, observation, and reflection, with Cycle II incorporating adjustments based on Cycle I evaluations. Data collection encompassed test data on Mathematics learning outcomes and non-test data gathered through observation using instructor and student activity sheets. The study revealed significant improvements across both cycles. The STAD model's implementation provided a space for students to communicate, promoting an interactive learning environment and enhancing their understanding of Mathematics subjects. The research recommends further development and application of the STAD cooperative learning model in Grade V Mathematics. Teachers should optimize its usage by actively engaging students, addressing subject matter variations, and ensuring cooperative features are maintained. Additionally, the study serves as a foundation for future research on cooperative learning methods in various subjects and grade levels. In-depth examination highlighted critical aspects influencing the STAD model's effective application, including student interaction, preparation and evaluation in action cycles, improved conceptual knowledge, teacher involvement, and the impact of the learning context. Regular monitoring and assessment of the learning process, along with active student involvement in preparation activities, are crucial for successful implementation. This research contributes valuable insights into the efficiency of the STAD model in enhancing Mathematics learning outcomes at the primary school level, with positive implications for the quality of Mathematics teaching.